Be Positive and See Yourself Burdened with Debt? The Effect of Biased Expectations on (Over)-Indebtedness - Melanie Koch; Theres Klühs; Wiebke Stein (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Household over-indebtedness has increased worldwide. This study investigates one possible reason for this increase: biased income expectations. Thereby, we refer to the "permanent income hypothesis", which predicts that individuals borrow more today if they expect a higher income in the future. We collect data from an emerging country where over-indebtedness can be devastating, on the micro and the macro level. Furthermore, our sample of poor, rural households in Thailand is exposed to a high degree of uncertainty, which makes expectation formation prone to behavioral biases. Controlling for various household characteristics and employing several distinct measures for biased expectations and over-indebtedness, we find a strong and robust relationship between the two. In an additional lab-in-the-field experiment we explicitly find that overconfidence is related to overborrowing.
Keywords: D14; D84; D91; 330; Household over-indebtedness; Lab-in-the-feld experiment; Emerging markets